Natural Mode Constant Power Source for Manual Arc Welding - Shklovski, J.; Janson, K.; Sakkos, T. (Elektronika ir Elektrotechnika, 2012)
Energy growing demand and environmental issues put more emphasis on optimal energy use – by equipment and in process. In this paper a novel switch-mode load-resonant welding power source with output characteristic having constant power range is suggested. Due to the constant power operation and parametrical arc stability during manual welding process the better electrical and thermal performance and even weld bead could be obtained. The circuit of the suggested converter and criteria for its resonant components selection are given in order to describe proposed topology in relation to load conditions during welding. Theoretical and practical studies are conducted on experimental setup and first promising results have been obtained for given converter that are briefly presented and discussed. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2801